Method for testing interfacial shear strength of optical fiber embedded composite material based on annular pressure head
By combining annular and flat indenters, the interference of matrix plastic deformation on the test results was eliminated, solving the accuracy and reliability problems of fiber-composite material interface shear strength testing and realizing accurate calculation of fiber-composite material interface shear strength.
Patent Information
- Application Number
- CN202610070521.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-20
- Publication Date
- 2026-03-20
AI Technical Summary
Existing methods for testing the interfacial shear strength of optical fibers and composite materials suffer from problems such as clamping damage risk, difficulty in microdroplet positioning, stress concentration, and low repeatability and success rate of test data when applied to optical fibers, making it difficult to accurately measure the interfacial shear strength.
A method for testing the interfacial shear strength of fiber-embedded composite materials based on annular indentation heads is adopted. By comparing the test schemes of annular indentation and flat indentation, and combining the area ratio correction algorithm, the interference of matrix plastic deformation is eliminated, and the interfacial shear strength is calculated.
This significantly improves the accuracy and reliability of fiber-composite interface shear strength testing, avoids fiber breakage, obtains pure interface shear force, and ensures the stability and accuracy of test results.
Smart Images

Figure CN121702865A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of interface performance test of optical fiber and composite material, and particularly relates to a method for testing interface shear strength of optical fiber embedded in composite material based on a ring indenter. BACKGROUND
[0002] Optical fiber sensing intelligent composite material has broad application prospects in the fields of aerospace, intelligent sensing and high-end equipment manufacturing due to the excellent corrosion resistance, high sensitivity and multi-parameter sensing function of optical fiber. The interface between the optical fiber and the composite matrix as the link of load transmission, the interface shear strength directly determines the overall mechanical properties, long-term stability and failure mode of the intelligent material. Therefore, accurately characterizing the shear strength of the optical fiber-composite material interface has important guiding significance for material optimization and engineering application.
[0003] At present, the test methods for the interface shear strength of fibers and resin matrix at home and abroad mainly focus on the research on traditional reinforcing fibers such as glass fibers and carbon fibers, and there is no mature standard for testing the interface shear strength of optical fiber-composite material. The existing test methods mainly fall into two categories, but both have significant limitations when applied to optical fiber interface testing: The first category is the traditional pull-out test method, including single fiber pull-out method and fiber micro-drop debonding method. The basic principle is to pull out the fiber by axial external force to make the fiber-resin interface shear failure. However, this method has very high requirements for sample preparation and clamping precision. Since the optical fiber is brittle and has small stiffness, in the traditional single fiber pull-out test, the optical fiber body is prone to breakage before the interface failure, resulting in test failure. Although the micro-drop debonding method simplifies the preparation process, it still requires precise clamping and pulling of a single optical fiber, which not only faces the risk of clamping damage, but also has problems such as difficulty in positioning the micro-drop, low centering accuracy and difficulty in measuring small loads, making it difficult to ensure the repeatability and success rate of the test data.
[0004] The second category is the indentation method based on micro / nano indentation technology. The existing micro / nano indentation tester is usually equipped with a glass indenter or a conical indenter. These indenters have sharp ends, and when the indenter is driven to move downward to contact the surface of the optical fiber, high stress concentration will occur at the contact point. Due to the brittleness of the optical fiber, the optical fiber often breaks at the initial stage of indentation, which prevents the load from being transmitted to the interface through the indenter, and thus the interface shear strength cannot be accurately measured. SUMMARY
[0005] To solve the above technical problems, the present application provides a method for testing the interface shear strength of optical fiber embedded in composite material based on a ring indenter.
[0006] To achieve the above purpose, the technical scheme adopted by the present application is: A method for testing the interfacial shear strength of fiber-embedded composite materials based on an annular indenter is provided, comprising the following steps: Step 1: Provide samples: Provide Group A and Group B samples, both with a cross-sectional area smaller than the test head area; Group A samples are composite material samples with embedded optical fibers, and the end face of the optical fiber is coplanar with the surface of the substrate; Group B samples are composite material samples without embedded optical fibers. Step 2: Obtain ring compression data: Apply axial loading to the A group samples using a centrally hollowed-out annular indenter. The inner diameter of the annular indenter is greater than or equal to the diameter of the optical fiber, and its center is aligned with the optical fiber. Record the total load at which the load-displacement curve reaches the inflection point representing interface failure. and corresponding displacement ; Step 3: Obtain matrix data: Apply axial loading to the B group specimens using a flat-bottomed indenter and record the displacement when the loading reaches the specified value. Matrix compressive load at time ; Step 4: Calculate shear strength: Calculate the compressive load on the matrix based on the ratio of the effective compressive area of specimens in group A to that in group B. Corrections are made to obtain the equivalent compressive load on the matrix; the total load is then calculated. The difference between the interfacial shear force and the equivalent compressive load of the matrix is used to obtain the interfacial shear force, and then the interfacial shear strength is calculated.
[0007] Preferably, the compressive load on the matrix described in step four... The correction steps include: Given: ; in Since the deformation is constant, it can be deduced that, under the same compressive displacement, the area of the pressure field is directly proportional to the deformation. Therefore: ; in This represents the ring crush area of the sample in group A. This refers to the area of the sample in group B subjected to flat pressure. so: ; In the formula, The diameter of the cylindrical specimen section in group A; The inner diameter of the annular indenter; The diameter of the cylindrical specimen section in group B; For the matrix material of Group A test, the displacement The equivalent compressive load on the matrix that it bears.
[0008] Preferably, the formula for calculating the interfacial shear strength in step four is: ; wherein, is the interfacial shear strength; is the total load at the inflection point obtained by the ring indenter test; is the fiber diameter; is the fiber embedment depth.
[0009] Preferably, the specific way of aligning the center with the optical fiber in step two is: using the optical microscope integrated with the micro indenter to align the center point of the microscope field of view with the geometric center of the optical fiber cross section in the A group sample, and then controlling the center of the ring indenter to move to the geometric center.
[0010] Preferably, in steps two and three, the axial loading is in displacement control mode, and the loading rate is quasi-static rate; the inflection point of the interface failure appearing in the load-displacement curve recorded in step two is manifested as a significant mutation of the curve slope.
[0011] Preferably, the outer diameter of the ring indenter is greater than the cross-sectional diameter of the A group sample and the B group sample; during the loading process of steps two and three, the annular bottom surface of the ring indenter always completely covers the matrix region of the A group sample and the entire cross section of the B group sample, so as to produce overall axial compression deformation of the matrix material.
[0012] Preferably, the inner diameter of the hollow area in the middle part of the ring indenter is equal to or slightly larger than the diameter of the optical fiber in the A group sample, and the inner ring edge of the hollow area in the middle part is provided with a circular arc chamfer, and the curvature radius of the circular arc chamfer is adapted to the brittle characteristics of the optical fiber to avoid stress concentration.
[0013] Preferably, the A group sample and the B group sample are fixed on the sample seat of the micro indenter by vacuum chuck before testing; the axial direction of the optical fiber in the A group sample is parallel to the axial direction of the pure matrix cylindrical sample.
[0014] Preferably, the displacement amount in step two is set as a preset threshold value configured to cause complete shear failure of the optical fiber and the surrounding matrix interface while keeping the main structure of the matrix material from being broken or excessively compressed.
[0015] Preferably, the preparation process of the A group sample in step one includes: after embedding the optical fiber into the resin matrix and curing, using a diamond suspension to polish the test surface step by step until there is no stepped height difference between the end face of the optical fiber and the surrounding matrix surface, forming a continuous plane.
[0016] The present application provides a ring indenter-based optical fiber embedded composite material interface shear strength test method, and the beneficial effects of the present application are embodied in: The present application introduces a pure matrix sample (group B) with the same geometric size as a control group, uses a ring pressure (group A) and flat pressure (group B) comparison test scheme, and combines an area ratio correction algorithm to accurately deduct the matrix compression bearing effect from the total load. This method can obtain pure interface shear force, eliminate the interference of matrix plastic deformation on the test results, and significantly improve the accuracy and reliability of the calculation results. BRIEF DESCRIPTION OF DRAWINGS
[0017] Figure 1 A schematic diagram of a fiber interface shear strength test for a micro indentation instrument (assembly ring loading head); Figure 2 A schematic diagram of a ring loading head and a composite sample; Figure 3 A schematic diagram of a ring loading head; Figure 4 A schematic diagram of the load direction; Figure 5 A load displacement curve diagram of the test results.
[0018] BRIEF DESCRIPTION OF DRAWINGS 1, micro indentation instrument; 2, load sensor; 3, ring loading head; 4, sample holder; 5, composite sample with embedded optical fiber; 6, sample stage; 7, ring loading head solid part; 8, ring loading head middle hollow area; 9, matrix area of the composite sample with embedded optical fiber; 10, optical fiber; 11, vacuum chuck. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present application will be described clearly and completely below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0020] Please refer to Figures 1-5 The specific embodiments provided by the present application are as follows: The embodiments of the present application provide a fiber embedded composite material interface shear strength test method based on a ring loading head, including the following steps: Step one, providing a sample: providing group A samples and group B samples with a cross-sectional area smaller than the area of the test loading head; wherein the group A sample is a composite material sample with an embedded optical fiber, and the optical fiber end face is coplanar with the matrix surface; the group B sample is a composite material sample without an embedded optical fiber; Step two, obtain hoop stress data: use a center-hollowed ring-shaped indenter to apply axial load to the A group sample, the inner diameter of the ring-shaped indenter is greater than or equal to the fiber diameter and the center is aligned with the fiber; record the total load when the load-displacement curve appears a turning point representing interface failure and the corresponding displacement amount ; Step three, obtain matrix data: use a flat bottom indenter to apply axial load to the B group sample, record the matrix compression load when the load is applied to the displacement amount ; ; Step four, calculate shear strength: based on the ratio of the effective compression area of the A group sample to the B group sample, correct the matrix compression load to obtain the equivalent compression load of the matrix; calculate the difference between the total load and the equivalent compression load of the matrix to obtain the interface shear force, and then calculate the interface shear strength.
[0021] In this embodiment, the correction step of the matrix compression load in step four includes: It is known that: ; wherein is the deformation amount, so that the pressure force area is proportional under the same compression displacement, and therefore: ; wherein is the hoop stress force area of the A group sample, is the flat stress force area of the B group sample; Therefore: ; In the formula, is the cross-sectional diameter of the A group cylindrical sample; is the inner diameter of the ring-shaped indenter; is the cross-sectional diameter of the B group cylindrical sample; is the equivalent compression load of the matrix of the A group test matrix material under the displacement .
[0022] In this embodiment, the interface shear strength calculation formula in step four is: ; wherein, is the interface shear strength; is the turning point total load obtained by the ring-shaped indenter test; is the fiber diameter; is the fiber embedding depth.
[0023] Based on this, the application can completely avoid the optical fiber body during the test process by the central hollow annular indenter, only applies axial load to the resin matrix around the optical fiber, and forces the matrix to produce shear slip relative to the optical fiber. The technical bottleneck that the optical fiber-composite material interface strength is difficult to test by the indentation method for a long time is solved.
[0024] In addition, in the conventional indentation test, the measured load often mixes the interface shear force and the matrix compression resistance, which is difficult to separate. The application introduces a pure matrix sample (group B) with the same geometric size as a control group, uses the comparison test scheme of ring pressure (group A) and flat pressure (group B), combines the area ratio correction algorithm, and accurately deducts the matrix compression bearing effect from the total load. This method can obtain pure interface shear force, eliminate the interference of matrix plastic deformation on the test result, and significantly improve the accuracy and reliability of the calculation result.
[0025] Finally, the inner ring edge of the annular indenter is chamfered with a circular arc (R angle). Compared with the ordinary sharp edge, the stress concentration of the indenter on the root of the optical fiber or the resin matrix at the initial stage of pressing can be effectively eliminated, the indenter edge can be prevented from cutting the optical fiber or causing local collapse of the matrix like a cutter, and the stability of the test process is further ensured.
[0026] As shown in Figures 1 to 5 , the application also provides a specific embodiment, which specifically includes the following steps: S1: preparing two groups of composite material samples with consistent geometric sizes; Among them, group A is a composite material sample 5 with an embedded optical fiber 10; Group B is a composite material sample without an embedded optical fiber 10, and the cross-sectional area is smaller than that of the indenter.
[0027] Both groups of composite material samples are cylindrical, and the following geometric parameters of the two groups of samples are known: the diameter of the optical fiber 10 , the embedding depth of the optical fiber 10 , the diameter of the sample of group A , the cross-sectional diameter of the sample of group B , the inner diameter of the annular indenter 3 , the outer diameter of the annular indenter 3 , and the optical fiber 10 axis should be parallel to the cylindrical sample axis during sample preparation.
[0028] Among them, the sample parameters are: the diameter of the optical fiber 10 150um, the embedding depth 0.5mm, the diameter of the sample of group A 0.5mm, and the cross-sectional diameter of the sample of group B 0.5mm, ring indenter 3 inner diameter 150um, ring indenter 3 outer diameter 2mm.
[0029] S2: sample polishing; Specifically, the A group sample is placed on the stage 6 of the micro indenter 1. The test surface is finely polished using progressively finer sandpaper or diamond suspension. After polishing, it must be ensured that the upper and lower surfaces of the sample are flat and smooth, and the end face of the optical fiber 10 is at the same height plane as the surrounding matrix surface, forming a continuous surface without any steps.
[0030] S3: Install the vacuum chuck 11 at the center of the sample seat 4 of the micro indenter 1, and place the polished sample in the center of the chuck 11. Start the vacuum pump and gradually increase the suction force to ensure that the sample is firmly and smoothly adsorbed, avoiding any movement or vibration during the test.
[0031] S4: Ring indenter 3 installation; Specifically, the selected ring indenter 3 is installed to the lower end interface of the load sensor 2 of the micro indenter 1, and tightened according to the instrument procedure.
[0032] Confirm that the outer diameter or cross-sectional area of the ring indenter 3 is greater than the cross-sectional area of the sample, so that the load is borne by the entire end face of the sample.
[0033] Wherein, the ring indenter 3 includes a ring indenter body part 7 and a ring indenter middle hollow area 8.
[0034] S5: Optical positioning and centering; Specifically, using the high-power optical microscope integrated with the instrument, the cross section of the target optical fiber 10 is clearly found in the computer software. The automatic or manual positioning program of the instrument is executed to accurately align the center point of the ring indenter 3 with the geometric center point of the cross section of the optical fiber 10.
[0035] S6: Test parameter setting: select displacement control mode as loading mode; Specifically, a preset maximum displacement of 4um is set. The displacement should be sufficient to cause complete shear failure of the optical fiber-matrix interface, but at the same time avoid excessive displacement leading to the matrix region 9 of the composite material sample with embedded optical fiber itself being broken or the indenter excessively compressing the sample. The loading rate is set to a slower quasi-static rate of 50nm / s, so that the data acquisition system can clearly capture the load mutation signal corresponding to the interface failure on the load-displacement curve.
[0036] S7: Test execution and data acquisition; Specifically, the upper magnetic drive and displacement system of the micro indenter 1 will automatically control the loading of the annular indenter 3 according to the set parameters, and record the load in real time at a high frequency P and displacement h data. Observe the real-time curve, when the load curve appears obvious slope mutation, indicating that the interface has occurred major failure, the test program can be stopped, and the total load of the curve inflection point is recorded and the corresponding displacement .
[0037] The measured value is 2.126N, and the corresponding displacement is 1.98um. The flat bottom indenter is used to measure pure pressure, which contains pressure and shear force.
[0038] S8: After the test is completed, the displacement system of the micro indenter 1 is used to lift the annular indenter 3 to a safe height to avoid collision with the sample. Turn off the vacuum pump and remove the sample that has completed the test.
[0039] S9: After all the annular indenter 3 tests are completed, the annular indenter 3 is lifted to a safe height, and the annular indenter 3 is disassembled according to the operation procedure.
[0040] S10: sample switching and processing; The composite sample of group B (without optical fiber) is placed on the sample stage 6 of the micro indenter 1. The test surface is treated by the same grinding and polishing process as S2 to ensure the consistency of the surface state.
[0041] S11: flat bottom indenter installation and fixation; The flat bottom indenter is installed at the lower end of the load sensor 2 of the micro indenter 1 to simulate uniform compression of the matrix material. The sample is firmly fixed by using the vacuum chuck 11.
[0042] S12: optical positioning; Use a high-power optical microscope to accurately align the flat bottom indenter with the geometric center of the sample cross section.
[0043] S13: test parameter setting, also select displacement control mode; Also set the maximum displacement to 4um, load to the displacement of at the same displacement control mode and rate as the annular indenter test to ensure that the load data corresponding to the displacement can be obtained. Start the test program, and the instrument automatically performs loading and records the load-displacement data.
[0044] The loading rate is set to the same quasi-static rate as the annular indenter test to ensure consistency of experimental conditions.
[0045] S14: After the test is stopped, the indenter is raised to a safe height, the vacuum pump is turned off, and the sample is removed.
[0046] As shown in FIG. 6, from the load-displacement curve, the load value corresponding to the displacement of 0.198 um is recorded as 1.36 N. Figures 4 to 5 At this time, the load of the flat-bottom indenter is 1.36 N. To obtain the load value corresponding to the ring-shaped area under the ring compression, the load value F is mathematically processed as follows: The corresponding cross section is a circular force surface with a radius of 0.5 mm. To obtain the load value corresponding to the ring-shaped area under the ring compression, the load value F is mathematically processed as follows: In the formula, D is the cross-sectional diameter of the A group sample; D is the inner diameter of the ring-shaped indenter; D is the cross-sectional diameter of the B group sample; D is the equivalent cross-sectional compression displacement of 0.198 um; The load represents the compression load of the ring compression test matrix under the displacement of 0.198 um. The above-mentioned 0.5 mm, the cross-sectional diameter of the B group cylindrical sample is 0.5 mm, the inner diameter of the ring-shaped indenter 3 is 155 um,
[0047] 0.198 um is the ring compression test displacement result. 1.36 N is the load value when the flat-bottom indenter is displaced to 0.198 um. The calculated value is 1.3 N, which is the compression load under the same cross-sectional area and compression displacement, i.e., the compression load under the displacement of 0.198 um in the ring compression test.
[0048] S15: Calculate the shear strength of the optical fiber-composite material interface based on the following formula: The above-mentioned is the test curve inflection point load (N) of the ring-shaped indenter 3; is the optical fiber diameter (um); is the optical fiber embedding depth (mm); is the interface shear strength, and the value is 3.507 MPa.
[0049] While embodiments of the application have been shown and described, it is to be understood that the embodiments described are merely exemplary of the principles and application of the present application. Numerous modifications and adaptions can be effected without departing from the spirit and scope of the present application, which is not limited to the exact construction and arrangement described. It is intended, therefore, to cover all modifications and adaptions that fall within the scope of the claims and their equivalents.
Claims
1. A method for testing the interfacial shear strength of fiber-embedded composite materials based on an annular indenter, characterized in that, Includes the following steps: Step 1: Provide samples: Provide Group A and Group B samples, both with a cross-sectional area smaller than the area of the test indenter. Among them, Group A samples are composite material samples with embedded optical fibers, and the end face of the optical fiber is coplanar with the surface of the substrate; Group B samples are composite material samples without embedded optical fibers. Step 2: Obtain ring compression data: Apply axial loading to the A group samples using a centrally hollowed-out annular indenter. The inner diameter of the annular indenter is greater than or equal to the diameter of the optical fiber, and its center is aligned with the optical fiber. Record the total load at which the load-displacement curve reaches the inflection point representing interface failure. and corresponding displacement ; Step 3: Obtain matrix data: Apply axial loading to the B group specimens using a flat-bottomed indenter and record the displacement when the loading reaches the specified value. matrix compressive load at time ; Step 4: Calculate shear strength: Calculate the compressive load on the matrix based on the ratio of the effective compressive area of specimens in group A to that in group B. Corrections are made to obtain the equivalent compressive load on the matrix; the total load is then calculated. The difference between the interfacial shear force and the equivalent compressive load of the matrix is used to obtain the interfacial shear force, and then the interfacial shear strength is calculated.
2. The method for testing the interfacial shear strength of fiber-embedded composite materials based on a ring-shaped indenter according to claim 1, characterized in that, The compressive load on the matrix described in step four The correction steps include: Given: ; in Since the deformation is constant, it can be deduced that, under the same compressive displacement, the area of the pressure field is directly proportional to the deformation. Therefore: ; in This represents the ring crush area of the sample in group A. The area of the sample in group B subjected to flat pressure. so: ; In the formula, The diameter of the cylindrical specimen section in group A; The inner diameter of the annular indenter; The diameter of the cylindrical specimen section in group B; For the matrix material of Group A test, the displacement The equivalent compressive load on the matrix that it bears.
3. The method for testing the interfacial shear strength of fiber-embedded composite materials based on a ring-shaped indenter according to claim 2, characterized in that, The formula for calculating the interfacial shear strength in step four is: ; in, Interfacial shear strength; The total load at the inflection point obtained from the annular indenter test; The diameter of the optical fiber; This refers to the depth at which the optical fiber is embedded.
4. The method for testing the interfacial shear strength of fiber-embedded composite materials based on a ring-shaped indenter according to claim 3, characterized in that, The specific method for aligning the center and the optical fiber in step two is as follows: using an optical microscope integrated with a micrometer indenter, align the center point of the microscope's field of view with the geometric center of the optical fiber cross-section in the sample of group A, and then control the center of the annular indenter to move to that geometric center.
5. The method for testing the interfacial shear strength of fiber-embedded composite materials based on a ring-shaped indenter according to claim 3, characterized in that, In steps two and three, the axial loading adopts displacement control mode, and the loading rate is quasi-static rate; the interface failure inflection point of the load-displacement curve recorded in step two is manifested as a significant abrupt change in the slope of the curve.
6. The method for testing the interfacial shear strength of fiber-embedded composite materials based on a ring-shaped indenter according to claim 3, characterized in that, The outer diameter of the annular indenter is larger than the cross-sectional diameter of the samples in groups A and B. During the loading process in steps two and three, the annular bottom surface of the annular indenter always completely covers the matrix area of the sample in group A and the entire cross-section of the sample in group B, causing the matrix material to undergo overall axial compression deformation.
7. The method for testing the interfacial shear strength of fiber-embedded composite materials based on an annular indenter according to claim 3, characterized in that, The inner diameter of the hollowed-out area in the middle of the annular pressure head is equal to or slightly larger than the diameter of the optical fiber in the A group sample, and the inner ring edge of the hollowed-out area is provided with a rounded chamfer. The radius of curvature of the rounded chamfer is adapted to the brittle characteristics of the optical fiber to avoid stress concentration.
8. The method for testing the interfacial shear strength of fiber-embedded composite materials based on a ring-shaped indenter according to claim 3, characterized in that, Before testing, both Group A and Group B samples were fixed to the sample holder of the micron indenter using a vacuum suction cup; the optical fiber axis in Group A sample was parallel to the cylindrical axis of Group A sample.
9. The method for testing the interfacial shear strength of fiber-embedded composite materials based on a ring-shaped indenter according to claim 3, characterized in that, The displacement amount mentioned in step two A preset threshold is set, which is configured to cause complete shear failure at the interface between the optical fiber and the surrounding matrix, while keeping the main structure of the matrix material from breaking or being excessively compressed.
10. The method for testing the interfacial shear strength of fiber-embedded composite materials based on a ring-shaped indenter according to claim 3, characterized in that, The preparation process of the A group samples in step one includes: embedding the optical fiber into the resin matrix and curing it, then polishing the test surface step by step with diamond suspension until there is no step height difference between the end face of the optical fiber and the surrounding matrix surface, forming a continuous plane.